2019
DOI: 10.1186/s12879-019-4196-8
|View full text |Cite
|
Sign up to set email alerts
|

A viral genome wide association study and genotypic resistance testing in patients failing first line antiretroviral therapy in the first large countrywide Ethiopian HIV cohort

Abstract: Background Antiretroviral therapy (ART) was rolled-out in Ethiopia in 2005, but there are no reports on outcome of ART and human immunodeficiency virus drug resistance (HIVDR) at national level. We described acquired drug resistance mutations in pol gene and performed a viral genome wide association study in virologic treatment failure patients who started first line ART during 2009–2011 in the first large countrywide HIV cohort in Ethiopia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…The high prevalence of DR in NNRTIs may related to widespread use of efavirenz in the initial regimen in this study. Of concern, 50.39% participants in our study showed dual-class resistance (NNRTIs and NRTIs), which was similar to the patterns of studies reported from other studies from low and middle-income countries [27][28][29].…”
Section: Discussionsupporting
confidence: 89%
“…The high prevalence of DR in NNRTIs may related to widespread use of efavirenz in the initial regimen in this study. Of concern, 50.39% participants in our study showed dual-class resistance (NNRTIs and NRTIs), which was similar to the patterns of studies reported from other studies from low and middle-income countries [27][28][29].…”
Section: Discussionsupporting
confidence: 89%
“…Proviral HIV-1 RNA was extracted from serum samples using the QIAamp Viral RNA mini Kit ® (Qiagen, Hilden, Germany) following the manufacturer's instructions, and the cDNA was sequentially obtained using the Superscript III RT-PCR kit (Invitrogen, CA). Fragments of the pol gene were generated by PCR according to a previously reported (18,19) . Strict laboratory precautions were taken to avoid cross contamination.…”
Section: Laboratory Measurementsmentioning
confidence: 99%
“…The national HIV treatment guideline requests screening for baseline HBV serology (HBsAg) [ 25 ] But HBV diagnosis before initiation of HIV treatment and close monitoring of patients on for HBV viremia and biochemical status are not implemented in Ethiopia. Mutation and rapid progression of drug resistance, exacerbation of HBV disease and liver enzyme flare are the potential risks in this high HIV/HBV burden area [ 26 , 27 ]. This study did not assess the effect of 3TC because all the study participants were exposed to the drug, tested once and not followed for HBV response.…”
Section: Discussionmentioning
confidence: 99%